Life Satisfaction in Patients with Critical Limb Ischemia Following Vascular Surgery and Endovascular Therapy - Muhammad Shoaib Khan, Asadullah Awan, Irfan Ali, Rabia Gilani, Nida Jawad, Sheikh Qais Falah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this research is to assess the efficacy of vascular surgery and endovascular therapy for critical limb ischemia. Study Design: Prospective study Place and Duration: This prospective study was conducted at Dow International Medical College and Dow University of Health Sciences, OJHA Campus, Karachi in the period from April, 2022 to September, 2022. Methods: Total 90 patients had critical limb ischemia were presented. All the patients were enrolled after taking informed written consent. Included patients were admitted for revascularization and divided equally in two groups. Group I received vascular surgery in 45 cases and 45 cases of group II received endovascular treatment (PTA). At 3 months post-revascularization, all patients were evaluated using the ankle-brachial index (ABI), the 6-minute walking test, and the Nottingham Health Profile (NHP) questionnaire. SPSS 22.0 was used to analyze all data. Results: The mean age of the included cases in group I was 64.6±5.57 years and in group II mean age was 69.5±8.44 years. There were majority males 33 (73.3%) in group I and 36 (80%) in group II. Comorbidities were DM, HTN, Hyperlipidemia and CAD among all cases. ABI and 6-minute walking distance improved significantly three months after the treatment in both groups. At six months post-procedure, both groups had similar NHP Part I and Part II total scores. However, the surgical revascularization group had substantially higher domain scores in social isolation and physical abilities with p value <0.012. Conclusion: Our findings indicate that patients undergoing surgical revascularization or PTA for SFA stenosis have comparable overall scores on the NHP questionnaire three months after revascularization. Subjects who undergo surgical revascularization score significantly higher than those who undergo percutaneous transluminal angioplasty (PTA) on the NHP's social isolation and physical ability dimensions. Keywords: Peripheral bypass surgery, Peripheral arterial disease, Quality of life, Endovascular treatment